Ventilatory complications in neonates in the Neonatal Intensive Care Unit: an integrative review (Research, Society and Development, 2022)
Mechanical ventilatory support in the Neonatal Intensive Care Unit (NICU) is a crucial intervention for the survival of newborns with respiratory assistance demand. However, there may be complications arising from treatment. Therefore, this study aims to search, analyze and synthesize, through the integrative literature review method, articles on ventilatory complications that occurred in neonates during hospitalization in the Neonatal Intensive Care Unit, published from 2017 to 2022, in national and international literature. A survey was carried out using the following search strategies: “Mechanical Ventilation”, “Respiratory Complications”, “Neonatal Intensive Care Units”; AND “neonatal NICU”, in the following electronic databases: National Library of Medicine (PubMed), Web of Science, Scopus, Virtual Health Library – BVS (Bireme), Scientific Electronic Library Online (Scielo) and Cochrane, as well as an additional search in gray literature, through Google Scholar and Open Grey. The methodological analysis was performed using the Critical Review Form – Quantitative Studies. Considering the eligibility criteria, after reading and analyzing the articles in full, three studies were included in this review. The ventilatory complications commonly described were: pneumothorax, bronchial pulmonar dysplasia, pneumonia and pulmonary hemorrhage. There is a scarcity of studies published in the period from 2017 to 2022 on the subject, highlighting the need for more research, with specific methodological detail, which can contribute to the improvement of the performance of multidisciplinary teams through evidence-based practice.